Pengaruh kompensasi dan lingkungan kerja terhadap kinerja karyawan PT. Jasa Barutama Perkasa Pekanbaru - Fronica '; Susi Hendriani; Dewita Suryati Ningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this research is to examine the influence of compesation and working environment to employee performance of PT. Jasa Barutama Perkasa Pekanbaru. This research use compesation and working environment as independent variable, and employee performance as dependent variable. The population of this research are all employees of PT. Jasa Barutama Perkasa Pekanbaru which amounted to 42 respondents and all of them will be used as a sample of this research. Data analysis method in this research is descriptive analysis. The result of using descriptive analysis is the compesation and working environment are affect the performances of employees at PT. Jasa Barutama Perkasa Pekanbaru. This indicates that the two independent variables had a significant effect on the dependent variable.Keywords : Compesation, Working Environment, and Employee Performance.